EFFECT OF SOME SEED TREATMENTS ON GERMINATION OF Sideritis perfoliata L. - Olcay Arabacı; Feride Yaşar; Neval Gül Öğretmen; Uğur Tan (Trakya University Journal of Natural Sciences, 2016)
The genus Sideritis L. belonging to Lamiaceae family is represented with more than 150 species worldwide.. The genus is represented in Turkey by 46 species and 53 taxon within two sections among which 39 are endemic. Endemism rate (79.5%) in Turkey is quite high because Turkey is one of the two major gene centers of the genus. Sideritis species are known among people with different local names such as mountain tea, highland tea, sage, sarıkız tea and tail tea. According to some recent researches, extracts obtained from Sideritis species were shown to have antistress, antiulcer, analgesic, antioxidant, antibacterial, anti-inflammatory and insecticidal effects. The interest in and the demand for this plant species has increased particularly due to its antioxidant effect. Seed germination studies of this species have great importance on determination of production strategies of medical and aromatic plants. This study was conducted to determine the effects of some pre-treatments (ethylene, gibberellin, mannitol, seaweed and cold pre-treatment) on germination of Sideritis perfoliata L. which is naturally grown in western Anatolia. The study was carried out at 25/15oC day/night temperature conditions. The experiments were performed according to completely randomized design with 3 replications at Adnan Menderes University, Faculty of Agriculture, Field Crops Laboratory. Significant differences were determined between applications with respect to germination rates and germination vigor values.